PROPOSED BUSINESS STRATEGY FOR RADAR PROGRAM IN PT LEN INDUSTRI (PERSERO) - Barokah, Billy
Through strategic projects, both those that have been created by the government and supporting government priority programs, Len will act as a development agent and contribute to both defense independence and economic improvement. Radar, submarine, rocket, missile, medium tank, combat aircraft, and propellant are the seven priority independence programs that have been announced. The Indonesian government, in this case the Ministry of SOEs, has a discourse to select Len as a pioneer in growing the Indonesian radar sector to assist the growth of the domestic manufacturing industry for civilian radar and defense radar. This study focuses on the strategy of increasing national radar manufacturing capabilities and infrastructure development so that Len may become an independent radar manufacturing industry with a viable radar business portfolio. To fulfill its mandate of creating national radar capabilities, Len must overcome significant obstacles, including a lack of cash flow, a small presence in manufacturing and R&D, a reliance on debt to fund operations, a shortage of engineering talent, and a lack of advanced infrastructure.